A novel scientometric approach to elucidated giant panda frontier research - Mohd Noor, Mohd Iqbal; Amir Mustafa, Amira Mas Ayu; Haidi, Yang; Ramlee, Mohd Noor Afiq; Abdullah, Mohd Tajuddin (Universiti Teknologi MARA (UiTM), 2023)
Giant panda conservation was one of the most successful in situ and ex situ conservation efforts in the world. The exclusivity herbivory evolution of Ailuropoda melanolueca from the Ursidae family sparks many interests in the dietetics research of said panda. Utilising data from 1079 Scopus and Web of Science-indexed journals from 1990 to 2020, this research conducted a depth scientometrics analysis for authors, countries and institutions conducting research closely related to giant pandas. Next, the study emphasises the burst analysis, cluster analysis and co-citation analysis to determine the top countries, research institutions, researchers and direction of research trends in Ailuropoda melanolueca research and its derivatives. The result shows from the exponential trend of research literature produced in the past 50 years that the Republic of China has dominated giant panda research, and second, in line is the United States of America. Based on overlay in trend analysis, there is substantial potential in economic-related research involving giant panda conservation.